Recovery of base metals from a sulphate-based bioleach solution using commercially available chelating ion exchange resins and adsorbents - Liebenberg, Cornelius Johannes (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScEng)--Stellenbosch University, 2012.